Das altkirchenslavische Wort. Bildung, Bedeutung, Herleitung Altkirchenslavische Studien Teil 1 - Birnbaum, Henrik (Slavistische Beitraege, 1997)
The purpose of this study is to close a gap that still exists, by summarizing all aspects of the Old Church Slavonic vocabulary except for inflection, with the compilation of stem formation, semantics, and etymology. new points of view arose.